Learning Dynamics NAV patterns : create solutions that are easy to maintain, are quick to upgrade, and follow proven concepts and design /: create solutions that are easy to maintain, are quick to upgrade, and follow proven concepts and design. (September 2015) - Brummel, Mark
No abstract available